What are the gender differences in risk and needs of males and females sentenced for white-collar crimes? - Goulette, Natalie (Criminal justice studies, 2020)
Reducing recidivism rates continues to be the focus of scholars and practitioners alike. While the risk-need-responsivity (RNR) principle model has guided correctional treatment services for nearly 40 years, some scholars argue that it does not necessarily pertain to special groups of people, more specifically women or people who commit white-collar offenses. The current study examines differences in risk scores for males and females who were convicted of federal white-collar crimes and who were placed on community supervision. Differences between males and females were noted, suggesting that gender-specific risk-needs assessment tools should be considered for women generally, and women sentenced for white-collar crime specifically.